Pengaruh Komposisi Katalis H-Zeolit Dan Kecepatan Pengadukan Terhadap Karakteristik Isopropil Oleat - Ardiana, Amalia; Nirwana, Nirwana; HS, Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Crude palm oil uses to term downstream industries in indonesia still at low, because of that we need to develop in downstream products. In addition, one of them which developed is fatty acid alkyl ester. Downstream products that included in fatty acid alkyl ester is plastisizer. Plastisizer is additive substance that added into polymer to increase flexibility and workability with esterification process. esterification is process between carboxiclic acid and alcohol to form ester and water as byproduct. In this research, plastisizer synthesized by esterification of oleic acid and isopropanol with activated natural zeolit as catalyst. This process was doing with variation of stirrer speed (175, 200 and 225 rpm) and composition of catalyst (12.5, 15 and 17.5%) also as fixed variable is temperature of reaction at 75 - 80°C, the reaction time of 6 hours and molar ratio of 1:9 oleic acid based. From esterification analysis result we can look that strirrer speed and composition of catalyst influenced rate of reaction to reach the equlibrium. The best operating condition in this reasearch has got at 17.5% composition of catalyst and 200 rpm of stirrer speed that produce 59.27% conversion. Product that has been produced is methyl ethyl ester, oleic acid, Methyl Ester, Dihidroxypropyl Ester and Isopropyl Ester. Characteriztion of plastisizer that has produced from this research is viscosity at (200 C ) is 4,360 – 5,882 mPa.s and specific gravity (200 C) is 0,785 – 0,844. Keywords: Esterification, H-Zeolit , Isopropanol, Oleic Acid, Plasticizer